Surgical Cryoablation of Drug Resistant Ventricular Tachycardia and Aneurysmectomy of Postinfarction Left Ventricular Aneurysm - Marek Pojar; Jan Harrer; Nedal Omran; Martin Vobornik (Case Reports in Medicine)
Heart failure is usually associated with left ventricle remodelling, wall thickening, and worsening of the systolic function. Ventricular tachycardia is a common and a negative prognostic factor in patients with endocardial scarring following myocardial infarction and aneurysm formation. The authors present a case of a 51-year-old man with ischemic heart disease, who suffered myocardial infarction four years ago. The patient was admitted to the hospital with sustained ventricular tachycardia despite maximal pharmacotherapy and also underwent unsuccessful percutaneous radiofrequency ablation in the right ventricle. Transthoracic echocardiography revealed left ventricle dysfunction with ejection fraction of 25%, aneurysm of the apex of the left ventricle with thrombus formation inside the aneurysm. Surgical therapy consisted of the cryoablation applied at the transitional zone of the scar and viable tissue and the resection of the aneurysm. The patient remained free of any ventricular tachycardia four months later.